2020
DOI: 10.3390/cancers12123837
|View full text |Cite|
|
Sign up to set email alerts
|

Overcoming the Hurdles of Autologous T-Cell-Based Therapies in B-Cell Non-Hodgkin Lymphoma

Abstract: The next frontier towards a cure for B-cell non-Hodgkin lymphomas (B-NHL) is autologous cellular immunotherapy such as immune checkpoint blockade (ICB), bispecific antibodies (BsAbs) and chimeric antigen receptor (CAR) T-cells. While highly successful in various solid malignancies and in aggressive B-cell leukemia, this clinical success is often not matched in B-NHL. T-cell subset skewing, exhaustion, expansion of regulatory T-cell subsets, or other yet to be defined mechanisms may underlie the lack of efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 223 publications
(338 reference statements)
0
8
0
Order By: Relevance
“…Third, the expanded effector cell populations must persist-both in sufficient quantity and activity-until the entirety of the malignant cell cohort is eliminated. T-cell persistence is multifactorial and heavily influenced by the balance of receptor signaling, cytokine stimulation, and memory T-cell differentiation [97,98]. Finally, an ideal immune response is one that generates immunologic memory so that future encounters with the TAA can be recognized and eliminated swiftly before creating complications for the patient.…”
Section: Activation Persistence Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the expanded effector cell populations must persist-both in sufficient quantity and activity-until the entirety of the malignant cell cohort is eliminated. T-cell persistence is multifactorial and heavily influenced by the balance of receptor signaling, cytokine stimulation, and memory T-cell differentiation [97,98]. Finally, an ideal immune response is one that generates immunologic memory so that future encounters with the TAA can be recognized and eliminated swiftly before creating complications for the patient.…”
Section: Activation Persistence Memorymentioning
confidence: 99%
“…Vaccines to promote tumor antigen presentation on dendritic cells continue to be studied as well [160]. Finally, adoptive cell therapies have ushered in a new era of cellular immunotherapy, with chimeric antigen receptor (CAR) Tcells approved for several B-cell neoplasms and numerous additional CAR-T and CAR-NK cell products under clinical investigation [97,98,161].…”
Section: Engaging the Antitumor Immune Responsementioning
confidence: 99%
“… 9,10 We have shown that CD8 T cells in CLL have impaired glucose metabolism upon activation and decreased mitochondrial fitness in the resting state, 7,11 both of which could contribute to the low efficacy of T cell–based therapies in CLL. 12 Although a clear relation between metabolism and function was recently described in CD8 T cells of patients with CLL, 7 CD4 T-cell metabolism remains an unexplored but important issue to address, because these cell types can play distinct roles in CLL.…”
Section: Introductionmentioning
confidence: 99%
“…The authors integrate clinical data from trials using ICIs, bispecific antibodies, and CAR-T cells with T-cell alterations observed in B-NHL patients. The authors list possible solutions to overcome T-cell dysfunction (such as exhaustion and skewing or the expansion of regulatory T cells), including combination therapies with immunomodulatory drugs (IMIDs) or improvement of CAR-T-cell manufacturing to maximize their persistence [ 2 ]. Alternatively, strategies engaging innate immune cells to fight B-cell malignancies represent an attractive and rapidly evolving field.…”
mentioning
confidence: 99%